Criminalization Vol. II : Where Do We Go from Here? - Balyan, Chirag; Pal, Garima (Social Sciences E-Books Online, Collection 2025., 2025)
In this second of two volumes, Criminalization: Where Do We Go from Here embarks on an exploration of the historical roots of over criminalization. It traces its origins back to ancient legal systems and societal norms, elucidating the evolution of the legal framework alongside shifting attitudes and policy decisions. The chapters shed light on the socio-cultural forces that have contributed to the proliferation of criminal laws, resulting in a state of over criminalization in contemporary society, supported by empirical analysis. See Less